SOME HISTOLOGICAL STUDIES ON THE PANCREATIC ISLET CELLS IN TURKEY (Maleagris gallopavo) - Hussain, Kh. A. (The Iraqi Journal of Veterinary Medicine, 1998)
Pancreatic islets of Turkey were different from those of mammals. It is divided into alpha, beta and mixed types according to the ground of cellular composition. The alpha islets are composed of A-cells and D-cells. Whereas the beta islets are composed of B-cells and D-cells. The mixed islets were composed mainly of B-cells, a few D-cells and A-cells. APP cells were not obvious.